2017
DOI: 10.18203/2349-3291.ijcp20174181
|View full text |Cite
|
Sign up to set email alerts
|

Study of sleep pattern in children aged 1-12 years attending OPD at tertiary care hospital, Puducherry, India

Abstract: Background: Children differ in their sleep pattern from adults and within their developmental age groups. Good sleep habits help them in better sleep outcomes. Inadequate sleep can contribute to various health issues. Hence, this study was carried out to find out sleep pattern in children and identify factors affecting it so that suitable measures can be taken to ensure good sleep hygiene in children.Methods: This was a cross-sectional observational study done in children aged 1-12 years. Every 5th child who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The practice of cosleeping forms a natural part of parenting in eastern culture [ 16 , 17 ], and the finding is similar in our study which showed that a large number of young children sleep with their parents in the same bed. The finding is further supported by the findings of a study done in India which reported that cosleeping is about 97.5% [ 6 ]. Though supine sleep position is generally recommended for infants to prevent the risk of sudden infant death syndrome (SIDS) [ 18 ], in our study, the most common sleeping position was found to be lateral.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The practice of cosleeping forms a natural part of parenting in eastern culture [ 16 , 17 ], and the finding is similar in our study which showed that a large number of young children sleep with their parents in the same bed. The finding is further supported by the findings of a study done in India which reported that cosleeping is about 97.5% [ 6 ]. Though supine sleep position is generally recommended for infants to prevent the risk of sudden infant death syndrome (SIDS) [ 18 ], in our study, the most common sleeping position was found to be lateral.…”
Section: Discussionsupporting
confidence: 78%
“…Behavioral sleep disorders may manifest as sleep onset delay, sleep interruptions, early morning awakening, or a combination of these [ 5 ]. Research studies have shown that sleep problems are common in up to 10.5% in toddlers, and the most common problem in these young children is difficulty in falling asleep [ 6 ]. Sleep problems, consequently, can lead to inattention [ 7 , 8 ] and hyperactivity among children leading to daytime sleepiness [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weekend oversleep can dysregulate the circadian rhythm and prolong school night sleep onset latency. [2569101112] The sleep duration decreased with increasing age and grades. Another study done among urban adolescents showed similar results of sleep disturbances and deprivation with increased age and grades.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with findings of the study done in Puducherry. [5] Decreasing parental supervision and academic pressure among highly educated may be a reason behind this. There is paucity of data from developing country settings to do comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation